2020
DOI: 10.1002/jbt.22467
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐rich water alleviates cyclosporine A‐induced nephrotoxicity via the Keap1/Nrf2 signaling pathway

Abstract: Oxidative stress induced by long-term cyclosporine A (CsA) administration is a major cause of chronic nephrotoxicity, which is characterized by tubular atrophy, tubular cell apoptosis, and interstitial fibrosis in the progression of organ transplantation.Although hydrogen-rich water (HRW) has been used to prevent various oxidative stress-related diseases, its underlying mechanisms remain unclear. This study investigated the effects of HRW on CsA-induced nephrotoxicity and its potential mechanisms. After admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In 2011, Kamimura et al reported that prolonged consumption of HW significantly controlled fat and body weights in db/db obese mice by stimulating energy metabolism [ 152 ]. A recent study revealed that H 2 attenuated allergic inflammation in a mouse model of allergic airway inflammation by reversing an energy metabolic pathway switch from oxidative phosphorylation to aerobic glycolysis [ 153 ].…”
Section: Preventive and Therapeutic Applications Of Hmentioning
confidence: 99%
“…In 2011, Kamimura et al reported that prolonged consumption of HW significantly controlled fat and body weights in db/db obese mice by stimulating energy metabolism [ 152 ]. A recent study revealed that H 2 attenuated allergic inflammation in a mouse model of allergic airway inflammation by reversing an energy metabolic pathway switch from oxidative phosphorylation to aerobic glycolysis [ 153 ].…”
Section: Preventive and Therapeutic Applications Of Hmentioning
confidence: 99%
“…Growing evidences have shown that the Kelch-like ECH-associated protein 1 (Keap1)/nuclear factor erythroid 2-related factor 2 (Nrf2)-signal pathway plays crucial roles in oxidative stress related cardiovascular disease by regulating heme oxygenase 1 (HO1) and NADPH dehydrogenase quinone 1 (NQO1) [ 10 , 11 ]. Nrf2 is inhibited by binding with Keap1 in cytoplasm under physiological state.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, HRS significantly decreased the protein expression of cytosolic Nrf2, while increased in the expression of nuclear Nrf2, but the total expression of Nrf2 did not increase in rats treated with. 59 These results indicated that hydrogen protects against oxidative stress injuries via the activation of the Keap1/Nrf2 signaling pathway.…”
Section: Hydrogen Inhibits Apoptotic Cascadesmentioning
confidence: 91%